Stress Management of Jamaah in the Digital Era: Integrating Qur’anic Psychology and Contemporary Da’wah Strategies - Werna Hendri Nopayana; Koharudin; Yanto Supono; Meity Suryandari (Journal of Education and Learning Sciences, 2026)
The rapid development of digital technology has intensified social interaction through digital media, but it has also led to the emergence of digital stress affecting the psychological and spiritual conditions of mad’u. This study examines how stress in the digital era can be managed through Qur’anic psychology and how contemporary da’wah strategies can be integrated to address this issue. This research employs a qualitative approach using library research by analyzing relevant scholarly literature. The findings indicate that digital stress is influenced by factors such as information overload, social media pressure, and social comparison. Qur’anic psychological concepts such as sabr (patience), tawakkal (trust in God), and dhikr (remembrance of God) are proven to be effective as spiritual coping strategies in managing stress. The study concludes that integrating Qur’anic psychology with contemporary da’wah strategies provides a holistic approach to developing mentally resilient and spiritually grounded mad’u in the digital era.